2008
DOI: 10.2503/jjshs1.77.33
|View full text |Cite
|
Sign up to set email alerts
|

An Anthocyanin Regulator from Grapes, VlmybA1-2, Produces Reddish-Purple Plants

Abstract: A cDNA, VlmybA1-2, for an anthocyanin regulatory gene of grape was constructed under the control of the cauliflower mosaic virus (CaMV) 35SRNA promoter and introduced into leaf disks and petioles of kiwifruit (Actinidia deliciosa) plants by Agrobacterium-mediated gene transfer. When the tissues were cultured on selection medium, red cells visible to the naked eye formed at the cut ends of the segments after approximately 2 weeks. The cells developed into calluses, adventitious buds, and reddish-purple plantlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…These results are presumably due to both the toxic effects of PA and disturbance by PA oxidization, because previous reports showed that phenolic compounds and their oxidation cause the browning of plant tissue and physically disturb regeneration (Madhusudhanan and Rahiman, 2000;Tang and Newton, 2004;Johkan et al, 2008). The transformation of many fruit crops, such as apple, grapevine, kiwifruit, and persimmon, depends on adventitious bud regeneration from leaves or calluses in vitro (Maheswaran et al, 1992;Matsuta et al, 1993;Scorza et al, 1995;Tao et al, 1997;Koshita et al, 2008). However, our results suggested that it is difficult to regenerate transgenic plants with DkMyb4 via adventitious buds in vitro.…”
Section: Application Of Ectopic Dkmyb4 Expressionmentioning
confidence: 68%
See 3 more Smart Citations
“…These results are presumably due to both the toxic effects of PA and disturbance by PA oxidization, because previous reports showed that phenolic compounds and their oxidation cause the browning of plant tissue and physically disturb regeneration (Madhusudhanan and Rahiman, 2000;Tang and Newton, 2004;Johkan et al, 2008). The transformation of many fruit crops, such as apple, grapevine, kiwifruit, and persimmon, depends on adventitious bud regeneration from leaves or calluses in vitro (Maheswaran et al, 1992;Matsuta et al, 1993;Scorza et al, 1995;Tao et al, 1997;Koshita et al, 2008). However, our results suggested that it is difficult to regenerate transgenic plants with DkMyb4 via adventitious buds in vitro.…”
Section: Application Of Ectopic Dkmyb4 Expressionmentioning
confidence: 68%
“…Koshita et al (2008) demonstrated the effective functional analysis of grape (Vitis labruscana) Myb TF VlMYBA1-2, the regulator of anthocyanin biosynthesis, by kiwifruit transformation (Hayward). The anthocyanin and PA biosynthetic pathways share almost all structural genes except for the last catalytic steps ( Fig.…”
Section: Analysis Of Pa Biosynthesis In Camv35s-dkmyb4-transformed Kimentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that UFGT is a key enzyme and that VlmybA genes induce anthocyanin biosynthesis in grape via expression of UFGT. Interestingly, VlmybA1-2 can also induce red cells in tissues of kiwifruit, tomato, and eggplant (Koshita et al, 2008).…”
Section: Isolation Of Transcription Factor Genes and Their Functionmentioning
confidence: 99%